To solve the equation 10x + 13 = -12, we need to isolate the variable x on one side of the equation. Here's how it can be done:
10x + 13 = -12
First, we subtract 13 from both sides to get rid of the constant term on the left side:
10x + 13 - 13 = -12 - 13
Simplifying, we have:
10x = -25
Next, we divide both sides by 10 to solve for x:
10x/10 = -25/10
Simplifying further:
x = -2.5
Therefore, the correct solution to the equation 10x + 13 = -12 is x = -2.5
The equation 10x+13=-12 is solved as follows supply the correct numbers to complete the solution
1 answer